Obtaining the circular polarization in a nano-dielectric resonator antenna for photonics applications. (3rd June 2019) - Varshney, Gaurav; Gotra, Shailza; Kaur, Jasleen; Pandey, V S; Yaduvanshi, R S
Abstract: A technique is implemented for obtaining the circular polarization in a nano-dielectric resonator (DR) antenna. A cylindrical DR has been excited by a nanostrip feedline. The application of input Gaussian pulse at the corner of feedline splits the field components into two parts. These field components travel at the edges of the feedline with a quarter wavelength path difference between them. The coupling of these field components to DR provides the circularly polarized response. The antenna is designed for operating in the optical C-band. The proposed antenna provides the 10 dB impedance bandwidth of 11.58% (187–210 THz) and 3 dB axial ratio bandwidth of 5.72% (188.5–199.6 THz).